Interactive e-learning lessons in patient-centred interview: an international multi-centred collaboration project piloted among dental and oral health students at the University of Otago, New Zealand - Olson, Hanna; Adam, Lee; Carrington, Samuel D.; Malmqvist, Sebastian; Christidis, Nikolaos; Clarke, Fiona; Jacobs, Reinhilde; Bostanci, Nagihan; Tawse-Smith, Andrew (IIUM Journal of Orofacial and Health Sciences, 2026)
This study examines the integration of e-learning tools into the Bachelor of Dental Surgery (BDS) and Bachelor of Oral Health (BOH) curricula at the University of Otago, aiming to enhance pre-clinical dental education. Through a multidisciplinary approach, our research team developed interactive e-learning lessons for pre-clinical dentistry skills, which were piloted among 15 BDS and BOH students in 2022. Students' feedback was gathered through focus group discussions allowing for qualitative analysis of their experiences. The findings indicated a strong potential for merging curricula across both programs, as similarities were identified in the didactic and simulated learning experiences. Students reported overwhelmingly positive interactions with the digital materials, highlighting enhancements in their engagement and motivation while expressing their desire for more interprofessional education (IPE). Suggested improvements included increasing collaborative learning opportunities and refining content delivery. This study informs the necessity of integrating e-learning tools within dental curricula to foster a collaborative educational environment that effectively prepares future dental professionals. Ultimately, it underscores the significance of aligning educational practices with contemporary learning methods including interprofessional education to improve patient care outcomes.